2010
DOI: 10.1179/147683010x12611460764129
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathology and lymphocyte subsets in patients with bulimia nervosa

Abstract: The association between lymphocyte subsets and several psychopathological variables which had proved to be able to affect immune cell count in other conditions was investigated in bulimia nervosa patients. Sixty-seven female bulimia nervosa patients and 29 female healthy controls were assessed for nutritional status (weight, blood cells, lymphocyte subsets, biochemical parameters and hormones) and psychopathology (anxiety, depression, hostility, impulsivity and borderline personality traits). A negative correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…Our ED patients also responded in a similar way, but with specific patterns of response: While in AN patients the decrease in the number of lymphocytes was similar to that in the HC, the process was three to four times more intense in the BN patients. We consider this discordance perhaps to be due to the existence of differences in the reactivity to stress of the HPA and SAM axes in AN and BN (Garaci et al, 2019; A. M. Monteleone et al, 2015, 2017; P. Monteleone et al, 2011, 2012, 2014; Nagata, Yamada, Iketani, & Kiriike, 2006; Paszynska et al, 2016; Pirke et al, 1992; Vaz‐Leal, Rodríguez‐Santos, García‐Herráiz, & Ramos‐Fuentes, 2011; Vaz‐Leal et al, 2007, 2010; Vaz‐Leal, Rodríguez‐Santos, García‐Herráiz, Monge‐Bautista, & López‐Vinuesa, 2011). In a recent study, we reported that AN‐restricting type patients display a pattern of stress‐induced cortisol release similar to that of healthy individuals, whereas a blunted cortisol response is observed in BN patients (Vaz‐Leal et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our ED patients also responded in a similar way, but with specific patterns of response: While in AN patients the decrease in the number of lymphocytes was similar to that in the HC, the process was three to four times more intense in the BN patients. We consider this discordance perhaps to be due to the existence of differences in the reactivity to stress of the HPA and SAM axes in AN and BN (Garaci et al, 2019; A. M. Monteleone et al, 2015, 2017; P. Monteleone et al, 2011, 2012, 2014; Nagata, Yamada, Iketani, & Kiriike, 2006; Paszynska et al, 2016; Pirke et al, 1992; Vaz‐Leal, Rodríguez‐Santos, García‐Herráiz, & Ramos‐Fuentes, 2011; Vaz‐Leal et al, 2007, 2010; Vaz‐Leal, Rodríguez‐Santos, García‐Herráiz, Monge‐Bautista, & López‐Vinuesa, 2011). In a recent study, we reported that AN‐restricting type patients display a pattern of stress‐induced cortisol release similar to that of healthy individuals, whereas a blunted cortisol response is observed in BN patients (Vaz‐Leal et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with ED are prone to use dysfunctional and ineffective coping methods (Brytek‐Matera & Schiltz, 2013; Ghaderi & Scott, 2000; Hernando et al, 2019; Jaúregui‐Lobera, Estébanez, Santiago‐Fernández, Álvarez Bautista, & Garrido, 2009; Nagata, Matsuyama, Kiriike, Iketani, & Oshima, 2000; Tobin & Griffing, 1995; Troop, Holbrey, & Treasure, 1998). This seems to correlate with higher levels of depression, anxiety, and hostility (Dennard & Richards, 2013; Tobin & Griffing, 1995; Vaz‐Leal et al, 2007; Vaz‐Leal, Rodríguez‐Santos, Melero‐Ruiz, Ramos‐Fuentes, & García‐Herráiz, 2010), such that coping style seems to be able to identify and discriminate ED patients more effectively than the actual characteristics of the ED (Villa et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The resulting defects usually require comprehensive restorative or prosthodontic treatment. Eating disorders are associated with elevated levels of pro-inflammatory cytokines such as TNF-α and IL-6, indicating a psycho-neuroimmune interplay [92,93]. Also, eating disorders are related to psychological stress and inadequate coping behaviors and are often comorbid with other psychiatric disturbances such as anxiety and depression, with a probable bidirectional interaction [94].…”
Section: Eating Disorders: Anorexia and Bulimia Nervosamentioning
confidence: 99%
“…In addition, helper/cytotoxic T cell ratio negatively correlated in this group with impulsivity, hostility, and depression. In the light of these results, the potential influence of psychopathology on lymphocyte subset counts seems to be specific in BN patients, and more relevant than in healthy controls (Vaz-Leal et al, 2010). Moreover, the complement cascade, a major component of innate immunity, represents a driving force in the pathophysiology of multiple inflammatory disorders.…”
Section: Wwwintechopencommentioning
confidence: 99%